2012
DOI: 10.1590/s1413-86702012000100007
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human bocavirus 1 in infants with lower acute respiratory tract disease in Argentina, 2007 - 2009

Abstract: A B S T R A C T Human bocavirus (HBoV) is a parvovirus whose association with respiratory disease is currently under investigation.Objective: To determine HBoV prevalence in children with lower acute respiratory infection. Results: The general prevalence of HBoV was 21.5% and the positive cases (HBoV+) were more frequent during winter and spring. The mean age of HBoV+ patients was 6.9 months, with 87.1% of the detections corresponding to infants less than 1 year old (among which the prevalence of HBoV was 26.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
1
16
0
4
Order By: Relevance
“…Human Bocavirus (HBoV) was discovered in 2005, in Sweden by Allander and colleagues by using a largescale molecular viral screening technique including DNase sequence-independent single-primer amplification [6]. Since initial observations, several studies have reported the prevalence of human Bocavirus infection all over the world ranging from 2 to 21.5%, mainly in children younger than 3 years of age where it has been associated with upper and with lower RTIs [64][65][66][67][68][69]. In a study from Norway, HBoV was detected in 12% of children with RTI and it was the fourth most common virus after RSV, HRV and hMPV [70].…”
Section: Bocavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Bocavirus (HBoV) was discovered in 2005, in Sweden by Allander and colleagues by using a largescale molecular viral screening technique including DNase sequence-independent single-primer amplification [6]. Since initial observations, several studies have reported the prevalence of human Bocavirus infection all over the world ranging from 2 to 21.5%, mainly in children younger than 3 years of age where it has been associated with upper and with lower RTIs [64][65][66][67][68][69]. In a study from Norway, HBoV was detected in 12% of children with RTI and it was the fourth most common virus after RSV, HRV and hMPV [70].…”
Section: Bocavirusmentioning
confidence: 99%
“…Prolonged viral shedding could explain both data reported in some papers in which HBoV DNA was found more often in asymptomatic than symptomatic cases [79,80] and the high percentage of co-infections. In fact, HBoV infections tend to be associated with high rates of coinfections with other viral pathogens such as HRV, adenoviruses, RSV, as well as with bacteria such as Streptococcus spp and Mycoplasma pneumoniae [46,54,[68][69][70]77,[81][82][83]. Characteristics of persistence and high frequency of coinfections have led to a debate over its role as a true pathogen [84].…”
Section: Bocavirusmentioning
confidence: 99%
“…They were hemoculture negative and also negative by molecular method (real time RT-PCR) for other common respiratory viruses, such as influenza A and B, parainfluenza 1, -2 and -3, adenovirus, respiratory syncytial virus and metapneumovirus . HBoV1 was confirmed by sequencing [Gen' database accession numbers JX034732 and JN632491 (Ghietto et al, 2012b]. Fifty-µl respiratory secretion was diluted in 500 µl Eagle's Minimum Essential Medium (EMEM) (GIBCO) with penicillin-streptomycin, centrifuged 3 min at 1000g and filtered.…”
Section: Inoculum Preparationmentioning
confidence: 99%
“…Human bocavirus 1 (HBoV1) belongs to the species Primate bocaparvovirus 1 in the genus Bocaparvovirus, subfamily Parvovirinae, family Parvoviridae (Qiu et al, 2017). It causes lower acute respiratory tract infections (ARTI) especially in infants less than 2 years old Martin et al, 2009;Meriluoto et al, 2012), and the frequency of detection varies from 1% to 33% (Bicer et al, 2013;Garcia-Garcia et al, 2008;Ghietto et al, 2012b;Martin et al, 2009). Severe cases are associated with high viral load, anti-HBoV1 IgM antibody detection or an increase in the levels of IgG antibodies, comorbidity and age (Christensen et al, 2010;Ghietto et al, 2015;Nascimento-Carvalho et al, 2012;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of HBoV infections ranges from asymptomatic 53,103,104 to mild upper respiratory infections 53,[105][106][107] up to serious and life threatening lower respiratory tract infections 56,95,[108][109][110][111][112][113][114][115][116][117][118] in all age groups. 56,57,95,104,[108][109][110][111][112][113][114][115][116][117][118][119][120][121] The immune response against HBoV starts with an IgM response followed by the formation of IgG, 99,100 but no life long immunity is generated in at least 40% of patients due to the original antigenic sin. 62,68,122 HBoV-1 is able to infect the central nervous system 82,84 and it has been identified as a putative cause of idiopathic lung fibrosis 44 supported by the fact that a set of pro...…”
Section: Clinical Featuresmentioning
confidence: 99%